NFTLock, a decentralised vault protocol for non-fungible tokens - T. Daranidarran (Nanyang Technological University, 2024)
Non-Fungible Tokens (NFTs) have emerged as a revolutionary asset class, offering digital ownership of unique art, entertainment, and collectables industries. They are held within cryptocurrency wallets and require permission to take specific actions or access certain digital assets. They leverage Blockchain technology's immutable and secure nature to ensure ownership, control and transparency. Over USD 100 million worth of NFTs have been publicly reported as stolen between July 2021 and July 2022 [1], creating an imminent need for robust security solutions within the ecosystem. Phishing, domain squatting, impersonation, and NFT swap scam threats pose significant risks to NFT owners, undermining trust and confidence in the wide-scale NFT adoption. At the time of the writing of this report, there are no solutions that act as active protection measures against the abovementioned threats. This report will detail and propose a viable solution, NFTLock, to mitigate risks and act as a safeguard for NFT owners. NFTLock addresses the critical need to ensure NFT security on the Ethereum blockchain by developing a decentralised vault protocol to safeguard NFTs. NFTLock’s Smart Contract acts like a vault that safeguards ERC721 tokens, protecting (locking) and disabling protection (unlocking) tokens at will. When a token is protected using the Locking Smart Contract, it will not be susceptible to the abovementioned risks. This Decentralised Application will instil confidence in NFT holders to carry out actions without the fear of potentially losing their high-value assets.